Rencana Pengelolaan dan Pemantauan Kualitas Udara Terhadap Rencana Kegiatan Pembangunan Permukiman - Muhammad Abdus Salam Jawwad; Zuhria Oktaviani (Prosiding ESEC, 2023)
Air pollution is the entry of harmful elements into the atmosphere, resulting in a deterioration of environmental quality. Dense settlements are one of the factors contributing to the decline in environmental quality. This study aims to formulate a plan for managing and monitoring air quality to minimize the impact of declining environmental quality in a settlement development project. The research method involves analyzing air quality based on ambient air quality test results, evaluating potential impacts based on parameters from ambient air quality tests, comparing the ambient air quality test results with relevant quality standards, and formulating a plan for air quality management and monitoring. Data collection techniques encompass qualitative and quantitative methods. Based on the analysis of ambient air quality test results at the location of the proposed settlement development project, the test values are higher compared to the surrounding areas of the project site, but they do not exceed the quality standards stipulated in Government Regulation Number 22 of 2021 concerning the Implementation and Management of the Environment, Annex VII Ambient Air Quality Standards. Therefore, the formulation of an air quality management and monitoring plan is essential, especially when the construction and operational phases of the settlement development project are underway. This effort aims to minimize air pollution that could degrade environmental quality and to support sustainable settlement development while considering environmental aspects.